China–Pakistan economic corridor (CPEC), tourism demand, and environmental concerns: Policy implications for sustainable tourism in Gilgit‐Baltistan. Issue 3 (24th January 2021) - Nazneen, Shama; Hong, Xu; Jenkins, Carson L.; Ud Din, Nizam
Abstract : The mega‐infrastructural development project provides easy access to remarkable tourism destinations and keeps attracting tourists. Tourist data from the tourism department of Gilgit‐Baltistan (GB), Pakistan, show that the China–Pakistan Economic Corridor (CPEC) project's impact positively relates to tourism demand. GB is at the early stage of tourism development, and residents show a willingness to support tourism even though tourism costs outweigh benefits. Besides, the existing tourism policy of Gilgit‐Baltistan focuses explicitly on economic sustainability but overlooks the socio‐cultural and environmental concerns. Therefore, the present study based on the stakeholder theory provides policy implications to minimize adverse effects on socio‐cultural and ecological resources and achieve sustainable tourism.